Computer games as a subject of psychological research – negative and positive aspects of gaming - Paleczna, Monika (Replay. The Polish Journal of Game Studies, 2022)
Computer games are an interactive form of entertainment that is popular with younger and younger players. Therefore researchers are actively seeking information on the consequences of pursuing this type of pastime. At the beginning, the researchers’ attention was focused mainly on the negative aspects of gaming. Nowadays, more and more benefits related to this activity are being indicated. In 2014, Granic, Lobel and Engels published an article on the benefits of playing computer games. The researchers focused on four areas: cognitive, motivational, emotional, and social. They wanted to inspire new research on mental health benefits of gaming by pointing to various research reports they selected. This paper aims to present the research directions explored in recent years by researchers who strive to describe the positive and negative consequences of gaming. I present the main directions and examples of research in these areas, highlighting the ambiguity of the current results. Problematic areas related to gaming include aggression and violence, addiction, weakening of social relations, experiencing undesirable emotions, sexualization, racial prejudice, and racial discrimination. The indicated opportunities and benefits are the strengthening of cognitive, motor, emotional, and social competences.